The influence of transformed Reynolds number suppression on gas transfer parameterizations and global DMS and CO2 fluxes - A. Zavarsky; C. A. Marandino (Atmospheric Chemistry and Physics, 2019)
Eddy covariance measurements show gas transfer velocity suppression at medium to high wind speed. A wind–wave interaction described by the transformed Reynolds number is used to characterize environmental conditions favoring this suppression. We take the transformed Reynolds number parameterization to review the two most cited wind speed gas transfer velocity parameterizations: Nightingale et al. (2000) and Wanninkhof (1992, 2014). We propose an algorithm to adjust k values for the effect of gas transfer suppression and validate it with two directly measured dimethyl sulfide (DMS) gas transfer velocity data sets that experienced gas transfer suppression. We also show that the data set used in the Nightingale 2000 parameterization experienced gas transfer suppression. A compensation of the suppression effect leads to an average increase of 22 % in the k vs. u relationship. Performing the same correction for Wanninkhof 2014 leads to an increase of 9.85 %. Additionally, we applied our gas transfer suppression algorithm to global air–sea flux climatologies of CO2 and DMS. The global application of gas transfer suppression leads to a decrease of 11 % in DMS outgassing. We expect the magnitude of Reynolds suppression on any global air–sea gas exchange to be about 10 %.